Kajian Etnobotani Wedang Tomboan Varian Abang Berbasis Kearifan Lokal di Situs Patirtaan Ngawonggo, Malang - Mia Andiarini; Nizar Vidya Arifani; Prima Dwi Purwanto; Rusdin Arifin Mangi Sarkoni; Fahrul Ghani Muhaimin; Heni Refdiana; Anas Bagaskara Witanto; Ayu Chandra Mustikasari; Nafi’ Windy Kharisma; Syifa Nabila Firdausya; Susriyati Mahanal (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Wedang tomboan variant abang is a traditional spice-based drink that developed at the Patirtaan Ngawonggo site, Tajinan District, Malang Regency as part of a local ethnomedicinal system that has been passed down from generation to generation. This study aims to identify the plant diversity, processing techniques, and nutritional content of wedang tomboan variant abang based on local knowledge of the local community. A qualitative descriptive approach was applied through field observations, in-depth interviews, documentation, and literature review. A total of 5 informants were selected using purposive sampling expanded with snowball sampling, consisting of 1 caretaker, 2 drink makers, and 2 consumers. The research results show that the red variant of Wedang Tomboan is composed of eight types of medicinal plants: lemongrass (Cymbopogon citratus), ginger (Zingiber officinale), cardamom (Amomum compactum), cinnamon (Cinnamomum verum), sappanwood (Caesalpinia sappan), black cumin (Nigella sativa), cloves (Syzygium aromaticum), and star anise (Illicium verum), which synergistically contain antioxidant, anti-inflammatory, and antimicrobial compounds. The preparation process involves boiling the fresh ingredients and steeping them in hot water, accompanied by a prayer ritual and counterclockwise stirring as a spiritual practice. This study confirms that the red variant of Wedang Tomboan represents an ethnobotanical knowledge system that integrates aspects of biodiversity, health, and the local cultural identity of the Ngawonggo people.